Dysregulation of the cohesin subunit RAD21 by Hepatitis C virus mediates host–virus interactions. Issue 5 (30th January 2019) - Perez, Shira; Gevor, Michael; Davidovich, Ateret; Kaspi, Antony; Yamin, Katreena; Domovich, Tom; Meirson, Tomer; Matityahu, Avi; Brody, Yehuda; Stemmer, Salomon M; El-Osta, Assam; Haviv, Izhak; et al.
Abstract: Hepatitis C virus (HCV) infection is the leading cause of chronic hepatitis, which often results in liver fibrosis, cirrhosis and hepatocellular carcinoma (HCC). HCV possesses an RNA genome and its replication is confined to the cytoplasm. Yet, infection with HCV leads to global changes in gene expression, and chromosomal instability (CIN) in the host cell. The mechanisms by which the cytoplasmic virus affects these nuclear processes are elusive. Here, we show that HCV modulates the function of the Structural Maintenance of Chromosome (SMC) protein complex, cohesin, which tethers remote regions of chromatin. We demonstrate that infection of hepatoma cells with HCV leads to up regulation of the expression of the RAD21 cohesin subunit and changes cohesin residency on the chromatin. These changes regulate the expression of genes associated with virus-induced pathways. Furthermore, siRNA downregulation of viral-induced RAD21 reduces HCV infection. During mitosis, HCV infection induces hypercondensation of chromosomes and the appearance of multi-centrosomes. We provide evidence that the underlying mechanism involves the viral NS3/4 protease and the cohesin regulator, WAPL. Altogether, our results provide the first evidence that HCV induces changes in gene expression and chromosome structure of infected cells by modulating cohesin.